What are the drivers of tetracycline photolysis induced by polystyrene microplastic? - Ding, Rui; Ouyang, Zhuozhi; Bai, Linjie; Zuo, Xin; Xiao, Chuanqi; Guo, Xuetao (Chemical engineering journal (Lausanne, Switzerland : 1996), 2022)
[Display omitted] •PS could accelerate the photolysis of TC at different pH.•1O2 and O2·- as major contributors, which enhanced the degradation of TC.•Aged PS accelerated the photolysis of TC due to the generation of EPFRs.•The degradation pathway of TC induced by PS was firstly proposed.•Five reaction pathways were presented based on identified products. Tetracycline (TC) and polystyrene microplastics (PS MPs), co-occurring in environments inevitably, have been frequently detected in a variety of environmental media. The two major types of emerging pollutants are attracting the global concern due to their potential threat to biota. PS can serve as carriers of TC in aquatic environments, thus dramatically altering environmental behavior of individual PS or TC. However, the photolysis of TC induced by PS remains unknown. In this study, kinetic experiments, quenching experiments, electron paramagnetic resonance analysis (EPR), Two-dimensional correlation Fourier transform infrared spectroscopy (2D-FTIR-COS) and products identification, were conducted to investigate effect and underlying mechanism of PS on photolysis of TC under sunlight irradiation. The corresponding results demonstrated that PS could induce photolysis of TC. The hydroxyl radicals (·OH), singlet oxygen (1O2) and superoxide anion (O2·-) enhanced degradation of TC. Quantitative quenching analysis revealed that both 1O2 and O2·- were main contributors, with contributions of 15.25 ± 2.21% and 11.69 ± 1.84%, respectively. Simultaneously, PS was aged during photolysis of TC, and the intension of O/C was enhanced from 2.07% to 17.92% with increasing aging time. Interestingly, we verified that highly aged PS significantly accelerated the photolysis due to generation of environmentally persistent free radicals (EPFRs), and the degradation pathway of TC induced by PS was firstly proposed. Subsequently, the transformation mainly included five reactions: hydrolysis, hydroxylation, deamination, demethylation and decarbonylation. This work provided a promising strategy for better understanding environmental fate of antibiotics and MPs.